2008
DOI: 10.1021/jo800583b
|View full text |Cite
|
Sign up to set email alerts
|

Homophymine A, an Anti-HIV Cyclodepsipeptide from the Sponge Homophymia sp.

Abstract: A new anti-HIV cyclodepsipeptide, homophymine A, was isolated from a New Caledonian collection of the marine sponge Homophymia sp. The structure of homophymine A was determined by interpretation of spectroscopic data, acid hydrolysis, and LC-MS analysis. Homophymine A contains 11 amino acid residues and an amide-linked 3-hydroxy-2,4,6-trimethyloctanoic acid moiety. Along with four D-, two L-, and one N-methyl amino acids, it also contains four unusual amino acid residues: (2S,3S,4R)-3,4-diMe-Gln, (2R,3R,4S)-4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 38 publications
2
68
0
Order By: Relevance
“…This b-branched framework, which characterizes all the members of this new class of non-ribosomal cyclodepsipeptides 5 , comprises the following: a 22-or a 25-membered macrolactone; the presence of complex and rare amino acids; a branching position occupied by a D-allo-b-hydroxy-a-amino acid acylated by the unique (2S,3S,4R)-3,4-dimethylglutamine (diMeGln) residue; and an N-terminus coupled to a saturated or unsaturated b-hydroxy acid. Examples of members of this family include callipeltin A 6 , papuamides 7,8 , neamphamides [9][10][11] , theopapuamides 12,13 , mirabamides 14,15 and homophymines 16,17 . Of note, all of them show relevant therapeutic profiles, mostly including potent cytotoxic and anti-HIV activities.…”
mentioning
confidence: 99%
“…This b-branched framework, which characterizes all the members of this new class of non-ribosomal cyclodepsipeptides 5 , comprises the following: a 22-or a 25-membered macrolactone; the presence of complex and rare amino acids; a branching position occupied by a D-allo-b-hydroxy-a-amino acid acylated by the unique (2S,3S,4R)-3,4-dimethylglutamine (diMeGln) residue; and an N-terminus coupled to a saturated or unsaturated b-hydroxy acid. Examples of members of this family include callipeltin A 6 , papuamides 7,8 , neamphamides [9][10][11] , theopapuamides 12,13 , mirabamides 14,15 and homophymines 16,17 . Of note, all of them show relevant therapeutic profiles, mostly including potent cytotoxic and anti-HIV activities.…”
mentioning
confidence: 99%
“…The marine peptides have been found to mainly inhibit viral entry through membrane fusion (Plaza et al, 2007 and2009;Zampella et al, 2008;Oku et al, 2004). The present study showed that a peptide isolated from S. maxima (SM-peptide) is noncytotoxic and inhibits HIV-1 IIIB -induced cell lysis, reverse transcriptase activity, and viral p24 antigen production.…”
Section: Discussionmentioning
confidence: 61%
“…Homophymine A contains 11 amino acid residues and an amide-linked 3-hydroxy-2,4,6-trimethyloctanoic acid moiety. In a cell-based XTT assay, homophymine A exhibited cytoprotective activity against HIV-1 infection with a IC50 of 75 nM 70 .…”
Section: Anti-hiv Peptidesmentioning
confidence: 99%